Investigation on the modeling and dynamic characteristics of a novel water hydraulic proportional valve driven by Voice Coil Motor - Han, Mingxing (Strojniški vestnik, 2021)
As the key control component of the water hydraulic systems, water hydraulic proportional valve has an important influence on the control performance of the systems. Due to the poor viscous and lubricity of water, the valve spool resistance is not only large, but also nonlinear. In this study, a novel fast-response water hydraulic proportional valve is presented. The actuator of the valve adopts voice coil motor (VCM), which has the advantages of fast response, high control precision and small volume. In order to realize the fast control of the valve, a lever amplifier is designed to obtain enough actuation force. A detailed and precise nonlinear mathematical model of the valve considering both the valve structural parameters and VCM electromagnetic characteristics is developed. A comprehensive performance simulation analysis has been carried out, which can be mainly divided into electromagnetic simulation, characteristics analysis of lever magnifier and dynamic performance simulation of the valve. The simulation results show that the adjusting time is about 28ms and the maximum overshoot is about 5%. The step response rise time is about 15ms. The test rig of the valve and VCM have been built, respectively. The test results of the prototype show that the optimal stroke range of VCM is 4mm ~15mm. The maximum overshoot of the valve is all around 10%, the adjusting time is about 30 ms in the opening process, and 35 ms in the closing process. The test results prove that the valve has good static and dynamic control performance.
Keywords: dinamična zmogljivost; dynamic performance; optimizacija; optimization design; proporcionalni krmilni ventili; proportional control valves; voice coil motors; zvočniške tuljave